The Relevance of Hadith about Teachers to 21st Century Education - Darnely; Ismail, Laode; Sakka, Abdul Rahman (Golden Ratio of Data in Summary, 2025)
This paper aims to analyze the relevance between the characteristics of the ideal educator according to the hadith and the demands of 21st-century education. Both modern educators and educators in Islam emphasize the importance of developing students' potential, building noble character, and creating a conducive learning environment. Modern educators are required to be lifelong learners, creative, innovative, and able to utilize technology. Meanwhile, educators in Islam must have sincere intentions, compassion, and noble character. Both also emphasize the importance of collaboration, flexibility, and a learner-centered approach.